Pendidikan Agama Islam Berorientasi Pada Problem Subyek Didik - Sutrisna, Sutrisna (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2013)
The study explores the implementation of student-oriented Islamic education.Â The study was conducted at three schools Kulon Progo regency: MAN I Kalibawang, MAN I and II Wates. Education design was made through school culture covering leadership and cultural model of the principals; religious human relation; roles of teachers and students; religious guidance and consoling; and comprehensive prayer guide. It was found out that the behaviors of the students changed. That is,Â the religiosity of the students was improving; smoking habit was decreasing; the discipline, responsibility and honesty were improving.